2020
DOI: 10.1037/str0000129
|View full text |Cite
|
Sign up to set email alerts
|

More than a simple pastime? The potential of physical activity to moderate the relationship between occupational stress and burnout symptoms.

Abstract: Researchers have emphasized the role of physical activity in accelerating recovery from stress. Therefore, the primary goal of the present study was to examine whether regular physical activity moderates the relationship between occupational stress and burnout symptoms in Swiss workers. 309 employees took part in the cross-sectional study. Occupational stress was operationalized with the job demands–control model and the effort–reward imbalance model. Physical activity was assessed via the International Physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 72 publications
4
29
2
2
Order By: Relevance
“…30 Regarding LTPA, although its bumpy dose-response relationship with WS is relatively difficult to interpret, first signs of reduction in WS seem to appear from the moment the METs-hour exceeds zero, stressing the relevance of merely practising a LTPA, regardless of the energy expenditure. This is in line with previous studies which have shown that people who engaged in more PA reported lower WS and fewer burnout symptoms, 12,18 yet without having established a dose-response relationship.…”
Section: Key Findingssupporting
confidence: 92%
See 1 more Smart Citation
“…30 Regarding LTPA, although its bumpy dose-response relationship with WS is relatively difficult to interpret, first signs of reduction in WS seem to appear from the moment the METs-hour exceeds zero, stressing the relevance of merely practising a LTPA, regardless of the energy expenditure. This is in line with previous studies which have shown that people who engaged in more PA reported lower WS and fewer burnout symptoms, 12,18 yet without having established a dose-response relationship.…”
Section: Key Findingssupporting
confidence: 92%
“…There is scientific evidence showing PA is negatively associated with WS and other health outcomes related with WS such as depression. 12 One explanation for that protective effect lies in the idea that PA consists of a recovery activity allowing the person to experience psychological detachment from the job demands and restore their depleted resources at work. 13 It is also well established that the neurophysiological correlates of PA such as the production of endorphins improve mood.…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity has been identified as one mechanism that mitigates the negative impact of stress on well-being and psychological functioning ( Brand et al, 2019 ; Ludyga et al, 2020 ; Sadeghi et al, 2020 ). Physical activity attenuates the association between occupational stress and burnout ( Gerber et al, 2020 ) and promotes emotional recovery from stressors ( Bernstein & McNally, 2017 , 2018 ). While physical activity is associated with lower levels of general perceived stress ( Brockmann et al, 2020 ; Ge et al, 2020 ), no studies to date have specifically examined whether physical activity attenuates the association between parenting stress and quality of life in working mothers, a population that is experiencing heightened levels of parenting stress during the COVID-19 pandemic.…”
mentioning
confidence: 99%
“…There may be two reasons for this. Commuting is, in some ways, like physical exercise, because it consumes time and energy ( Angrave et al, 2015 ; Gerber et al, 2020 ). People who do not regularly exercise may not do so due to time pressures.…”
Section: Discussionmentioning
confidence: 99%
“…For urban residents living in green space environment, physical exercise can promote their health ( Chen, Liu, Li, et al, 2017 ; Chen, Liu, Zhu, et al, 2017 ). Participants with higher physical activity levels reported fewer burnout symptoms when they experienced high levels of stress ( Gerber et al, 2020 ). Christian (2012) investigated people of full-time working age living in urban areas.…”
mentioning
confidence: 99%